Studi Komparasi Identifikasi Sumberdaya Alam di Wilayah Kepesisiran Gunung Kidul - Pahleviannur, Muhammad Rizal; Kinthen, Nabila; Novitasari, Henny; Purwitasari, Ihda Nurohmah; Jordan, Edgar (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study aims to determine the comparison of the potential naturalresources in the Gunungkidul Coastel Region. This study used a qualitativemethod by collecting data in the form of literature studies, documentation,and observation, using a questionnaire instrument, so that the datapresented is in the form of graphs. The result of this study are there is acomparison of the potential natural resources consisting of 1) land use, 2)pond fisheries, 3) mining, 4) industry, and 5) tourism business activities inthe Gunungkidul Coastel Region.Â